Prosthodontic Rehabilitation Alternative of Patients with Cleft Lip and Palate (CLP): Two Cases Report - Emrah Ayna; Emine Göncü Başaran; Köksal Beydemir (Hindawi Limited, 2009)
Although patients with cleft lip and palate (CLP) are not seen regularly in general dental practice, this is a frequent congenital anomaly; approximately one in every 800 live births results in a CLP. The cause of CLP is unknown, but possible causes are malnutrition and irradiation during pregnancy, psychological stress, teratogenic agents, infectious agents (viruses), and inheritance. Most clefts are likely caused by multiple genetic and nongenetic factors. Prosthetic reconstruction of the anterior maxilla is important for these patients. This paper describes the prosthetic rehabilitation of two patients with CLP, 19-year-old and 21-year-old women, both with surgically treated CLP. In both, an examination revealed a residual palatal defect of 2×3 mm and missing maxillary lateral incisors. The 19-year-old was treated with a fiber-reinforced composite resin-bonded fixed partial denture. The 21-year-old was treated with a removable partial denture with an extracoronal attachment system. The prosthetic rehabilitation of the two patients with CLP was evaluated clinically. In both, well-planned prosthetic, periodontal, and surgical therapy resulted in satisfactory function and esthetics, alleviating their deformities. With education and appropriate recall, the patients should be able to maintain their oral health.